Is PROGRESA working? summary of the results of an evaluation by IFPRI - Skoufias, Emmanuel; McClafferty, Bonnie (International Food Policy Research Institute, 2000)
In early 1998, the International Food Policy Research Institute (IFPRI) was asked to assist the PROGRESA administration to “determine if PROGRESA is functioning in practice as it is intended to by design.” This document summarizes the findings contained in a series of reports presented by IFPRI to PROGRESA from November 1998 through August 2000. A more detailed description of the research, rationale and methods appears in the list of supporting documents from which this document has been derived. In brief, the findings of IFPRI’s evaluation are that after just three years, the poor children of Mexico in the rural areas where PROGRESA is currently operating are more likely to enroll in school, are eating more diversified diets, getting more frequent health care and learning that the future may look quite different from the past. The majority of the evaluation findings suggest that PROGRESA’s combination of education, health, and nutrition interventions into one integrated package can be an effective means of breaking the intergenerational transmission of poverty. However, PROGRESA is still in its beginning stages. Many of the impacts of the program are likely to manifest themselves in the future. Clearly, the simultaneous intervention in the health and nutrition of 0 to 5 year old children of poor households today will positively reinforce school attendance, performance and attainment of children tomorrow. Thus, in addition to the benefits measured after three years of operation, it is likely that PROGRESA will have additional benefits in future years. Whether the vicious cycle of poverty and its intergenerational transmission are indeed broken can only be determined by continuing with PROGRESA and continuing to evaluate in the medium and long run its impact on the livelihood of Mexico’s poor. The possibility of expanding the coverage of PROGRESA to poor households in urban areas implies that there is opportunity to use program evaluation, such as that presented herein, as a means to adapt some of the components of the program to suit the needs of households in different environments. The IFPRI research team would encourage Mexico’s policy leaders to capitalize on the innovative precedent established by PROGRESA and to consider program evaluation as an indispensable component of all social policies.